Systematic attribution of heatwaves to the emissions of carbon majors - Yann Quilcaille; Lukas Gudmundsson; Dominik L. Schumacher; Thomas Gasser; Richard Heede; Corina Heri; Quentin Lejeune; Shruti Nath; Philippe Naveau; Wim Thiery; Carl-Friedrich Schleussner; Sonia I. Seneviratne (Nature, 2025)
Abstract Extreme event attribution assesses how climate change affected climate extremes, but typically focuses on single events 1–4 . Furthermore, these attributions rarely quantify the extent to which anthropogenic actors have contributed to these events 5,6 . Here we show that climate change made 213 historical heatwaves reported over 2000–2023 more likely and more intense, to which each of the 180 carbon majors (fossil fuel and cement producers) substantially contributed. This work relies on the expansion of a well-established event-based framework 1 . Owing to global warming since 1850–1900, the median of the heatwaves during 2000–2009 became about 20 times more likely, and about 200 times more likely during 2010–2019. Overall, one-quarter of these events were virtually impossible without climate change. The emissions of the carbon majors contribute to half the increase in heatwave intensity since 1850–1900. Depending on the carbon major, their individual contribution is high enough to enable the occurrence of 16–53 heatwaves that would have been virtually impossible in a preindustrial climate. We, therefore, establish that the influence of climate change on heatwaves has increased, and that all carbon majors, even the smaller ones, contributed substantially to the occurrence of heatwaves. Our results contribute to filling the evidentiary gap to establish accountability of historical climate extremes 7,8 .